2020
DOI: 10.1177/0309133320956631
|View full text |Cite
|
Sign up to set email alerts
|

Analysing and simulating spatial patterns of crop yield in Guizhou Province based on artificial neural networks

Abstract: The area of karst terrain in China covers 3.63×106 km2, with more than 40% in the southwestern region over the Guizhou Plateau. Karst comprises exposed carbonate bedrock over approximately 1.30×106 km2 of this area, which suffers from soil degradation and poor crop yield. This paper aims to gain a better understanding of the environmental controls on crop yield in order to enable more sustainable use of natural resources for food production and development. More precisely, four kinds of artificial neural netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 88 publications
1
11
0
2
Order By: Relevance
“…Regions dominated by magnesium-rich dolomite show the greatest annual variation in GPP, confirming previous work on the poor water storage capacity of the thin soil that has developed on dolomite (Liu et al, 2019). Liang et al (2021) find that the greatest effect on food production is temperature (16.4%), followed by radiation (15.3%), soil moisture (13.5%), fertilization of nitrogen (13.5%) and, finally, phosphorus (12.4%). In total, soil factors, including soil moisture and soil chemical features can contribute up to 40% of the crop yield.…”
supporting
confidence: 85%
“…Regions dominated by magnesium-rich dolomite show the greatest annual variation in GPP, confirming previous work on the poor water storage capacity of the thin soil that has developed on dolomite (Liu et al, 2019). Liang et al (2021) find that the greatest effect on food production is temperature (16.4%), followed by radiation (15.3%), soil moisture (13.5%), fertilization of nitrogen (13.5%) and, finally, phosphorus (12.4%). In total, soil factors, including soil moisture and soil chemical features can contribute up to 40% of the crop yield.…”
supporting
confidence: 85%
“…Improve nutrient use efficiency Nutrient cycling Soil N and P explained 13.5% and 12.4% of crop yield variances, respectively, at the Karst CZO (Liang et al, 2020); high risk of environmental pollution prevents increasing crop yield through fertilization (Liang et al, 2021) -Shift from "leaky" to "tight" N-cycling processes (D. Li et al, 2018) -Re-emergence of microbial N-cycling functions in soil after agricultural abandonment (D. Li et al, 2018Li et al, , 2021a 15 Farmers in all CZs identified fertilisers as their greatest cost and one of the top three farming challenges they face (Zheng et al,. 2018, this paper) 1,2 -Reduce N inputs to improve economic livelihoods and well-being -Judicious use of N with crop residue returns increases soil C (X. D. Song et al, 2019a;X.…”
Section: Zero-growth Action Plan For Chemical Fertilizers and Pesticidesmentioning
confidence: 99%
“…Furthermore, it has been proved that vegetation restoration activities do not necessarily reduce soil erosion in karst regions because climatic drought events threaten the sustainability of planting and its ability to conserve soil (Feng et al, 2021). Crop yield from an upper slope position would be greatly reduced by soil erosion (Liang et al, 2021), and this type of area may be one where forest planting activities such as those carried out by the Grain for Green project should first be applied. So far, however, the critical zone is only a statement of ‘concept’ rather than a systematic ‘science’, although 20 years have passed since this notion was first put forward in the book Basic Research Opportunities in Earth Science (An et al, 2016; National Research Council, 2001).…”
Section: From Karst Geomorphology To Critical Zone Sciencementioning
confidence: 99%